A Comprehensive Review on the Medicinal Benefits of Honey with an Emphasis on Unani Medicine - Khalid, Mohd; Husain, Nazim; Rahmatullah, Md; Alam, Abrar; Beg, Mohd U. (Current Traditional Medicine, 2023)
Background: Honey has been used medicinally in folk medicine since the dawn of civilization. It is a necessary component of medicine and food in a wide variety of cultures. It has been used in Unani Medicine for centuries to treat a variety of ailments. Objective: This review article aims to explore the medicinal characteristics of honey in view of Unani and modern concepts, highlight its potential in the treatment of the ailments stated in Unani medical literature, and also explore the relevant evidence-based phytochemistry, pharmacological, and clinical data. Methods: The authors searched classical texts exhaustively for information on the temperament (MizĦ#129;j), pharmacological activities, mechanism of action, and therapeutic benefits of honey. Additionally, a comprehensive search of internet databases was conducted to compile all available information on the physicochemical, phytochemical, and pharmacological properties of this compound. Results: Evidence suggests that honey contains about 180 different types of various compounds, including carbohydrates, proteins, enzymes, flavonoids, and other chemical substances. In Unani classical literature, it exerts important pharmacological actions besides its immense nutritional significance. Unani physicians advocated many tested/experimented prescriptions and formulations, which still have their relevance in the amelioration of various diseases. Conclusion: This analysis concludes that honey has been successfully utilized in Unani medicine for centuries to treat a variety of maladies and is a potential natural source of remedy for a variety of medical disorders. Future research on honey should include a combination of Unani and modern principles.
Keywords: antioxidant